A latent class model of residential choice behaviour and ethnic segregation preferences. Issue 4 (19th May 2018) - Ibraimovic, Tatjana; Hess, Stephane
Abstract: The nature of ethnic residential clustering involves diverse population segments which through their location decisions influence the spatial patterns of ethnic settlements. While residential location is in part determined by outside constraints, choice plays a role too, making the study of preferences an important research topic. Along with differences in socio-economic characteristics, literature often emphasizes the role of unobserved (behavioural) elements in the formation of preferences for ethnic neighbourhood composition. This paper tests the potential of latent class choice models to examine both observed and unobserved heterogeneity in residential choices across ethnic groups. The empirical example is estimated on stated preferences data from Lugano, Switzerland. The results indicate different ethnic attributes as key choice drivers for households belonging to three latent classes, where the origin of households is the best predictor of class membership. Swiss citizens are mainly concerned about high shares of foreigners, advantaged foreigners favour their co-nationals, while disadvantaged foreigners hold both of such preferences.